Lean accounting tools and competitive advantage in Jordanian industrial companies - Ayman Mohammad ALShanti; Khalil Mahmoud Ali Al-Refae; Mohammad Jebreel (Cogent Business & Management)
This study explores the impact of lean accounting tools—specifically value stream costing (VSC), target costing (TC), and kaizen costing (KCO)—on the competitive advantage (CA) of industrial companies in Jordan. We conducted an online survey targeting 400 managers across 32 companies, which yielded 293 responses from 18 companies. We validated the data, analyzed 279 complete responses using SPSS, and performed multiple regression analyses to test the study’s hypotheses. The results show a higher utilization of VSC and TC compared to KCO. Jordanian companies tend to focus on quality improvement (QI), time efficiency (TE), and operational reliability (OR) more than cost reduction (CR) and innovation (INN). A strong correlation exists between lean accounting tools (LAT) and competitive advantage. LAT has a significant effect on overall CA, with lean operations exerting the greatest influence, followed by VSC and TC. Although LAT significantly affects QI, INN, and TE, it does not have a significant impact on OR or CR.